Preventing Foodborne Illness: Listeriosis - Keith R. Schneider; Renée M. Goodrich-Schneider; Michael A. Hubbard; Dirk Sampath (EDIS, 2009)
Revised! FHSN-03-6, a 4-page fact sheet by Keith R. Schneider, Renée Goodrich-Schneider, Michael A. Hubbard, and Dirk Sampath, is one in a series of facts sheets discussing common foodborne pathogens of interest to food handlers, processors, and retailers. It answers questions about the causes of Listeria-associated foodborne illness, characteristics of the bacterium, how it is spread, foods associated with it, symptoms, high-risk populations, and sanitation methods for plants and food establishments. Includes references. Published by the UF Department of Food Science and Human Nutrition, August 2009.